1980
DOI: 10.1070/qe1980v010n04abeh010129
|View full text |Cite
|
Sign up to set email alerts
|

Excimer pulse-periodic laser

Abstract: The state-selective dissociation dynamics for anionic and excited neutral fragments of gaseous SiCl 4 following Cl 2p and Si 2p core-level excitations were characterized by combining measurements of the photoninduced anionic dissociation, x-ray absorption and UV/visible dispersed fluorescence. The transitions of core electrons to high Rydberg states/doubly excited states in the vicinity of both Si 2p and Cl 2p ionization thresholds of gaseous SiCl 4 lead to a remarkably enhanced production of anionic, Si − and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
1988
1988

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…2^4), followed by a more complete data set at d = 1.0 cm (Figs. [5][6][7][8][9][10][11][12][13][14].…”
Section: Resultsmentioning
confidence: 99%
“…2^4), followed by a more complete data set at d = 1.0 cm (Figs. [5][6][7][8][9][10][11][12][13][14].…”
Section: Resultsmentioning
confidence: 99%
“…At present, average output powers from 10 W to 200 W have been obtained by several researchers from transverse flow RGH lasers, with closed cycle or blowdown configurations [1][2][3][4][5][6][7]. The operating characteristics of these systems have shown that more than 5 gas replacements in the discharge volume between pulses are required to maintain the máximum energy per pulse.…”
Section: Introductionmentioning
confidence: 99%